2012
DOI: 10.1021/ja209931w
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Dynamics of an Unfolded Protein Examined by Molecular Dynamics Simulation

Abstract: The accurate characterization of the structure and dynamics of proteins in disordered states is a difficult problem at the frontier of structural biology whose solution promises to further our understanding of protein folding and intrinsically disordered proteins. Molecular dynamics (MD) simulations have added considerably to our understanding of folded proteins, but the accuracy with which the force fields used in such simulations can describe disordered proteins is unclear. In this work, using a modern force… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
210
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 229 publications
(226 citation statements)
references
References 26 publications
8
210
3
Order By: Relevance
“…Ultimately, it should be possible to address all of these aspects quantitatively in explicit-solvent molecular dynamics simulations. However, only recently are force fields and water models emerging that provide a reliable description of unfolded and disordered proteins (34,(74)(75)(76)(77)(78). We have shown that the temperature effects on unfolded state dimensions can be understood at a semiquantitative level by means of a molecular model with implicit solvent by including a temperature-dependent solvation free energy for the constituent amino acid residues.…”
Section: Resultsmentioning
confidence: 99%
“…Ultimately, it should be possible to address all of these aspects quantitatively in explicit-solvent molecular dynamics simulations. However, only recently are force fields and water models emerging that provide a reliable description of unfolded and disordered proteins (34,(74)(75)(76)(77)(78). We have shown that the temperature effects on unfolded state dimensions can be understood at a semiquantitative level by means of a molecular model with implicit solvent by including a temperature-dependent solvation free energy for the constituent amino acid residues.…”
Section: Resultsmentioning
confidence: 99%
“…These include the immense computer power required to reach the time scale at which foldon behavior emerges, the great accuracy required for the force fields used, and the need for a method that can extract a descriptive trace of the progression of the folding reaction. Recent advances in molecular dynamics trajectory analysis have transcended these limitations in part, bridged the divide between the micro-and macroscopic views of protein folding, and demonstrated that thermally driven amino acid-level searching leads to the native structure through the formation of native-like structural elements and their sequential incorporation in repeatable folding pathways (36)(37)(38). A recent approach explicitly uses foldon conservation and sequential stabilization in an iterative search strategy (39).…”
Section: Discussionmentioning
confidence: 99%
“…The unfolding and refolding of cooperative foldon units and their role in forming intermediates and pathways has been detected, in greater or lesser detail, in many proteins by HX methods (23-25, 29, 47-55), by sulfhydryl labeling (56,57), by relaxation dispersion NMR (58), and in theoretical simulations (36)(37)(38). The inherent cooperativity of native-like foldon units predisposes them rather than other fractional elements to account for the unit steps in protein folding and thus dictates the stepwise formation and native-like nature of pathway intermediates.…”
Section: Discussionmentioning
confidence: 99%
“…However, a higher-resolution view provided by experimental models (3)(4)(5)(6) and simulations (7) shows that the conformational ensemble is biased toward low-contact-order (CO) structures, e.g., α-helices, β-turns, and β-hairpins, which form and melt in less than a few microseconds. During folding, these nascent structures presumably coalesce into higher-order assemblies of ever-increasing free energy until reaching the transition-state ensemble (TSE) that leads to the native conformation.…”
mentioning
confidence: 99%